PERKEMBANGAN ANAK AUTIS RENDAH MENJADI ANAK AUTIS RINGAN DALAM MEMAHAMI TINDAK TUTUR DIREKTIF DI SLB AUTIS BUNDA MAKASSAR - Nurul Fitrah Yani (Cross-border, 2021)
This study aims to describe the development of the ability of children with low autism to become mild autistic children in understanding directive speech acts. This research is a case study research with qualitative descriptive analysis. The research location is at the Bunda Autism School. The data source is a child with autism who is added by a supervisor as a key informant. The duration of the study was two weeks, namely January 2020. The results of this study indicate that the ability of children with autism who used to be included in the category of severe autism has become mild autism. This certainly shows a rapid increase in the ability of children with autism to accept directive speech acts, namely being able to respond to TTD verbally and non-verbally.